Increasing the Effectiveness of Public Service Announcements Among Gen Z by Using Influencer Advertising - Pham, Nguyen T. (Journal of Applied Business and Economics, 2024)
In this study, we aim to explore the effectiveness of influencer advertising in the realm of public policy. More specifically, we will be examining key factors that can potentially increase psychological reactance among individuals belonging to Generation Z when they are processing anti-binge drinking Public Service Announcements. We then discuss how collaboration between federal agencies and social media influencers can overcome the hurdles posed by psychological reactance. By drawing upon the existing research on persuasive messages, psychological reactance, influencer advertising, and parasocial relationships, our findings will hold significant value for policymakers in disseminating impactful Public Service Announcements that resonate with Generation Z.